2017
DOI: 10.1186/s12934-017-0800-z
|View full text |Cite
|
Sign up to set email alerts
|

The expression and construction of engineering Escherichia coli producing humanized AluY RNAs

Abstract: BackgroundExogenous RNAs can specifically up-regulate or down-regulate gene expression after they enter into cells. Alu RNAs are the main constituent of human transcriptome and participate in gene expression regulation. AluY elements belong to a subfamily of Alus and are the youngest Alus. In this paper, we established the technology method of preparing genetically engineered humanized AluY RNAs (AluY RNAs) from Escherichia coli (E. coli) strains. This technology method also can be used to prepare other geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Extracellular tyrosinases production in soil environment are most likely involved in detoxification of phenolic compounds of plants, humid matter formation and polymerization [26].…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular tyrosinases production in soil environment are most likely involved in detoxification of phenolic compounds of plants, humid matter formation and polymerization [26].…”
Section: Discussionmentioning
confidence: 99%
“…Cell Culture and Cell Transfection HLECs (SRA01/04, Huatuo, Suzhou, China) were cultured in DMEM medium (4.5 g/L glucose, ThermoFisher Scientific, USA), supplemented with 10% fetal calf serum (FCS; ZETA TM Life, USA) under 5% CO 2 at 37℃. Yeast tRNA (tRNA) was purchased from Solarbio Life Sciences; Alu sense RNA (Alu RNA) and Alu antisense RNAs were prepared by our laboratory [26][27] . These Alu antisense RNAs include AluYas RNA, AluJBas RNA and AluSPas RNA.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies also indicated that murine SINE B1 antisense RNA retards the mouse aging process by removing accumulated ROS in senescent cells and regulating the expression of aging-associated genes [19] . Importantly, there are established methods for producing genetically engineered SINE RNAs that are of sufficient quality for cell and animal experiments [26][27] ; the availability of these methods means that nucleic acid reagents of treating aged-related diseases can be obtained. In this study, we examined whether human SINE antisense RNA (Aluas RNA) can protect human lens epithelial cells (HLECs) from apoptosis induced by MGO and sought to explore the mechanisms by which Aluas RNA could have this effect.…”
Section: Aluas Rna Ameliorates Apoptosismentioning
confidence: 99%